Seção Técnica de Comunicações - Trivellato, Regina Célia Franco; Santos, Patrícia Rosa Mendes dos; Zago, Mirian Barbosa (ARCHIVES OF HEALTH INVESTIGATION, 2013)
Apresentação - Regina Célia Franco Trivellato